Antibacterial activity of chemotherapeutic drugs against Escherichia coli and Staphylococcus pseudintermedius. (14th October 2019) - Campbell, O.; Gagnon, J.; Rubin, J.E.
Abstract: The ability of chemotherapeutic agents to affect the growth of common bacterial pathogens and the relationship between the effects of chemotherapeutics and antimicrobials is largely unknown. The purpose of this study was to describe the susceptibility of canine bacterial isolates to chemotherapeutic agents and to compare these results to their antimicrobial susceptibility. The effects of bleomycin, doxorubicin, cytarabine, cyclophosphamide, methotrexate, 5‐fluorouracil and gemcitabine on the growth of 33 Staphylococcus pseudintermedius isolates and 32 Escherichia coli isolates from dogs was determined by agar dilution. In addition to MICs, the lowest drug concentration associated with a decreased colony size was recorded. Results were compared to the MICs of a panel of antimicrobial agents. Bleomycin consistently inhibited bacterial growth of S. pseudintermedius and E. coli . Doxorubicin inhibited S. pseudintermedius but not E. coli while the opposite was seen for gemcitabine. Reduction in colony size on exposure to 5‐fluorouracil for both organisms, and methotrexate for S. pseudintermedius was seen. No observable effect of cyclophosphamide or cytarabine was observed. Associations between elevated MICs to chemotherapeutic drugs and antimicrobial resistance were not found. These results indicate that chemotherapeutic agents affect the growth of bacteria, but do not support a role in the selection of antimicrobial resistance. Significance and Impact of the Study: This study shows that chemotherapy drugs commonly used in veterinary oncology have an effect of the growth of canine isolates of Escherichia coli and Staphylococcus pseudintermedius . No associations between susceptibility to chemotherapeutic drugs and antibiotics were found, which does not support selection of antimicrobial resistance by chemotherapy drugs. Abstract : Significance and Impact of the Study: This study shows that chemotherapy drugs commonly used in veterinary oncology have an effect of the growth of canine isolates of Escherichia coli and Staphylococcus pseudintermedius . No associations between susceptibility to chemotherapeutic drugs and antibiotics were found, which does not support selection of antimicrobial resistance by chemotherapy drugs.